2010
DOI: 10.1002/stem.473
|View full text |Cite
|
Sign up to set email alerts
|

Concise review: Nanoparticles and cellular carriers-allies in cancer imaging and cellular gene therapy?

Abstract: Ineffective treatment and poor patient management continue to plague the arena of clinical oncology. The crucial issues include inadequate treatment efficacy due to ineffective targeting of cancer deposits, systemic toxicities, suboptimal cancer detection and disease monitoring. This has led to the quest for clinically relevant, innovative multifaceted solutions such as development of targeted and traceable therapies. Mesenchymal stem cells (MSCs) have the intrinsic ability to “home” to growing tumors and are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 225 publications
(237 reference statements)
1
45
0
Order By: Relevance
“…drug delivery and/or cancer therapy, see, for instance among recent overviews, [10][11][12][13][14]). Among these objects mixing organic and inor- It was shown that the O-K edge varies with the size of the particles [8], and this feature will be examined using Electron energy-Loss Near-Edge Structure (ELNES) simulations accounting for steps 1) to 3) previously enumerated.…”
Section: Gd 2 O 3 Npsmentioning
confidence: 99%
“…drug delivery and/or cancer therapy, see, for instance among recent overviews, [10][11][12][13][14]). Among these objects mixing organic and inor- It was shown that the O-K edge varies with the size of the particles [8], and this feature will be examined using Electron energy-Loss Near-Edge Structure (ELNES) simulations accounting for steps 1) to 3) previously enumerated.…”
Section: Gd 2 O 3 Npsmentioning
confidence: 99%
“…Recently, a number of studies have looked at magnetic targeting of cells. In cells/well) were incubated in 100 µl growth media for 24 h. Varying concentrations of SPIONs were added to vivo studies have shown that magnetic labeling, particularly with superparamagnetic iron oxide nanoparticles the wells and after 24 h MTT (Sigma) was added for 1 h. The media was removed and cells were incubated for (SPIONs), is relatively easy and safe (22,41,42). However, limited work has been done on using magnetic 1 h in the presence of dimethyl sulfoxide (DMSO; Sigma).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs show preferential migration toward sites of inflammation, injury, and cancer, suggesting that these cells may be attractive hypoimmunogenic cellular vehicles for drug and gene delivery [112], as well as trophic factors to damaged diabetic kidney.…”
Section: Perspectivesmentioning
confidence: 99%